Process Optimization and Mathematical Modeling of Cartridge Filter Cleanup Using Pulse Jet Air Ring (PJAR) Technology - Abdolreza Ansari; Alireza Pardakhti; Naser Mehrdadi (Environmental Energy and Economic Research, 2023)
Dust abatement is frequently performed using filters. The biggest challenge facing filter usage in different industries, is to sustainably clean and recycle them in order to reduce costs and increase filtration quality. A novel technology of Pulse Jet Air Ring (PJAR) has been invented in order to consume less time and energy, and to emit less pollutants into the air. In this method, a ring is installed around the filter body which is able to jet the air with a high speed in order to remove the dust around filter media. To get the best results, optimization of effective process parameters is necessary. Central composite design (CCD) of response surface methodology (RSM) is employed to optimize the cleanup process. Based on statistical analysis and optimization, the highest Pressure Difference percentage is accessible at the air pressure of 5.10 Bar, Velocity 43.00 m/s and Time 50.00 ms. The technique can be recommended as an economical as well as environmentally friendly technology.